PERANAN KOMPENSASI PKWT DAN BONUS AKHIR TAHUN DALAM MENINGKATKAN KINERJA KARYAWAN PADA PT. SURYARAYA RUBBERINDO INDUSTRIES - Muhammad Ferdy Ramdhan Rifulton; Mega Puspita Sari (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to determine the role of PKWT compensation and year-end bonuses in improving employee performance at PT Suryaraya Rubberindo Industries. This research uses descriptive qualitative research methods. Respondents in this study were 15 respondents consisting of contract employees of the wrapping & setting division of the packing section of PT Suryaraya Rubberindo Industries. The data collection methods used are observation, interview, and documentation. The data collected were analyzed descriptively by reducing data, presenting data, and drawing conclusions. The results of this study indicate that